2014
DOI: 10.14367/kjhep.2014.31.5.147
|View full text |Cite
|
Sign up to set email alerts
|

The association of depression and suicidal behaviors with smartphone use among Korean adolescents

Abstract: Objectives: This study aims to examine the association of depression, suicidal behaviors with smartphone use behaviors among Korean adolescents. Methods: We analyzed data from 'Youth Health and Life Skills Survey' in 2013. The survey was based on self-reported questionnaires distributed to 915 grade 7th and 8th students at four middle schools in Gangdong-gu, Seoul, Korea in 2013 to evaluate the effects of 'Youth Health and Life Skills' program. Depression and suicidal behaviors were measured in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…What is worth mentioning is that smartphone addiction was found to be positively correlated to depression, anxiety, stress, and suicidality at bivariate level. This result lends support to existing findings 25,32,34,41‐46 47 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…What is worth mentioning is that smartphone addiction was found to be positively correlated to depression, anxiety, stress, and suicidality at bivariate level. This result lends support to existing findings 25,32,34,41‐46 47 .…”
Section: Discussionsupporting
confidence: 91%
“…This result lends support to existing findings. 25,32,34,[41][42][43][44][45][46] To the best of our knowledge, there was only one local study stated that smartphone addiction was not associated with the severity of depression among young adults. 47 In the present hierarchical regression analysis, internet addiction emerged as the strongest predictor for all the dependent variables (ie, depression, anxiety, stress, and suicidality).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As concerns type of screen, a study conducted in 2013 showed that teenagers who had previously in their life experienced depression were more likely to use their cell phones more frequently than other adolescents (Kang & Lee, 2014).…”
Section: Discussionmentioning
confidence: 99%